Power efficiency of intensive cast iron desulfurization in a ladle - Сігарьов, Євген Миколайович (Eastern-European Journal of Enterprise Technologies, 2015)
The evaluation results of resource- and energy-saving efficiency of improved technological route "blast furnace - oxygen steel-making converter" for the conditions of PJSC "ArcelorMittal Kryvyi Rih" with the application of innovative technologies and devices for the pig iron desulphurization intensification in the ladle, converter melting using dual-flow oxygen lance, slag scull application on the converter lining were presented. The proposed method for sulfur removal from the pig iron before casting to converter provides secure insertion of dispersed magnesium deep into the melt with an intensity of more than 24 kg/min by increasing the interfacial contact surface of gas-magnesium bubbles with the melt at the movement of the lance nozzles, reduction of the specific reactant consumption and treatment duration by 20-25%, and increase in the degree of magnesium recovery to sulfur by 15-19% in comparison with the stationary lance. Using the proposed dual-flow lance design in converter melting improves the thermal balance and prevents process equipment metallization without reducing the unit lining resistance. Blowing of the final slag on the lining by moving gaspowder jets provides the regulation of physicochemical properties of the slag bath and formation of a skull protective layer of increased resistance. Expected cumulative reduction of energy costs in comparison with the standard technologies is 0.973 GJ/t of steel.